SARS‐CoV nucleocapsid protein binds to hUbc9, a ubiquitin conjugating enzyme of the sumoylation system - Fan, Zheng (J Med Virol, 2006)
SARS‐CoV is a newly identified coronavirus (CoV) that causes severe acute respiratory syndrome (SARS). The SARS‐CoV nucleocapsid (N) protein is an important structural and functional protein. To identify cellular proteins that interact with the SARS‐CoV N protein and to elucidate the possible involvement of N protein in SARS‐CoV pathogenesis, a human lymphocyte cDNA library was screened using a yeast two‐hybrid system assay. hUbc9, a ubiquitin conjugating enzyme of sumoylation system, was found to interact specifically with the N protein, implying the post‐translational sumoylation of the N protein. Mapping studies localized the critical N sequences for this interaction to amino acids 170–210, which includes the SR‐rich motif. However, the consensus motif of sumoylation GK(62)EE in the N protein is not responsible for binding to hUbc9. Mutations of hUbc9 at the enzyme active site C93A or C93S severely impair the interaction with the N protein. The two proteins were also shown to colocalize in the cytoplasm of the transfected 293T cells. This is the first report demonstrating the interaction of hUbc9 with a structural protein of plus‐strand RNA viruses, indicating a new drug target for SARS‐CoV. J. Med. Virol. 78:1365–1373, 2006. © 2006 Wiley‐Liss, Inc.